Nanocomposites formed by combination of urchin like NiS with Ni-nanoparticles/N-doped nanoporous carbon, derived from nickel organic framework, and decorated with RuO2 nanoparticles: Construction and kinetics for hydrogen evolution reaction. (20th September 2020) - Mohammadi Dehcheshmeh, Mohammad; Karimi Shervedani, Reza; Torabi, Mostafa
Highlights: A new urchin-like composite was formed by using NiS, Ni-NPS and N-nanoporous carbon. The composite set on GCE and decorated by RuO2, making GCE-NiS/Ni/NNPC/RuO2 electrode. The GCE-NiS/Ni/NNPC/RuO2 is an efficient electrocatalyst for the HER in alkaline solution. Improved activity was found to be originated from high surface area & synergistic effects . Abstract: Fabrication of active, stable, and cost effective electrocatalysts, as alternative cathodes to Pt or Pt-based materials for catalytic hydrogen production, is important for different industrial purposes, such as hydrogen therapy in medicine, syntheses in pharmaceutical and nutrient, and clean carbon-free energy carrier in industry. Herein, construction, characterization and examination of an efficient electrocatalyst for hydrogen evolution reaction (HER) in alkaline media is reported. The catalyst system is based on nanocomposites formed of urchin-like nickel sulfide incorporated with nickel nanoparticles and nitrogen doped-nanoporous carbon, and decorated electrochemically with ruthenium (IV) oxide on the glassy carbon electrodes, leading to GCE-NiS/Ni/NNPC/RuO2 system. Physicochemical characteristics of the prepared composite systems are studied by several surface, solution and electrochemical methods, from which the system is characterized. Then, electrocatalytic activity of the GCE modified with the composite, is studied for the HER by means of the steady-state linear sweep voltammetry (LSV), polarization curves (Tafel plots), and electrochemical impedance spectroscopy (EIS). The obtained data are analyzed by using appropriate equivalent circuit models, from which the HER kinetics are quantitatively determined. The results revealed that the electrode modified with the prepared composite, GCE-NiS/Ni/NNPC/RuO2, is an efficient electrocatalyst for the HER in alkaline solution, where an overpotential of −82.54 mV at the current density of 20 mA cm ‒2 (η20  =− 82.54 mV) with Tafel slope of 49.88 mV dec ‒1 is observed. These activities are very close to those obtained on Pt-based electrode materials. The origin of the enhancement in the HER activity can be attributed to (i) the high surface area of the urchin-like structure along with nanoporous carbon, and (ii) the synergistic chemical coupling effects between the NiS, Ni/NNPC and RuO2 nanoparticles . Graphical abstract: Image, graphical abstract